Cultural pluralism. (May 2015) - Bernstein, Richard J.
The expression 'cultural pluralism' was popularized by Horace Kallen, a student of William James. I explore the meaning of pluralism in the context of the American pragmatic tradition with emphasis on the meaning of pluralism for William James. Kallen sought to characterize cultural pluralism in contrast with the idea of America as a 'melting-pot'. I also examine the contributions of Randolph Bourne and the African-American philosopher Alain Locke to the discussion of cultural pluralism. I conclude by indicating that the idea of a democratic society that respects and is enriched by differences is highly relevant to contemporary discussions of cultural pluralism in a global context.